The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1161/01.str.0000136148.29490.fe
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Periodontal Pathogens and Stroke Risk

Abstract: Background and Purpose-The association between cerebrovascular events and periodontitis has been found in few studies based on clinical periodontal examinations. However, evidence on the association between periodontal pathogens and stroke is lacking. Therefore, the aim of the study was to investigate whether elevated levels of serum antibodies to major periodontal pathogens predict stroke in a case-control study. Methods-The study population comprised 6950 subjects (aged 45 to 64 years) who participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
17

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 23 publications
6
131
0
17
Order By: Relevance
“…These results are supported by recent studies showing that elevated serum anti-A. actinomycetemcomitans antibody levels predict stroke 28) and coronary heart disease. 29) A. actinomycetemcomitans possesses a number of putative virulence factors, including a leukotoxin that targets and destroys specific host immune cells (neutrophils and monocytes).…”
Section: Discussionsupporting
confidence: 81%
“…These results are supported by recent studies showing that elevated serum anti-A. actinomycetemcomitans antibody levels predict stroke 28) and coronary heart disease. 29) A. actinomycetemcomitans possesses a number of putative virulence factors, including a leukotoxin that targets and destroys specific host immune cells (neutrophils and monocytes).…”
Section: Discussionsupporting
confidence: 81%
“…In relation to CVD, increased levels of circulating antibodies towards periodontal bacteria, including both P. gingivalis and A. actinomycetemcomitans , have been associated with increased carotid intima-media thickness [18], and shown to be predictive of future myocardial infarction [19] and stroke [20]. Also, cross-sectional and case-control studies have reported positive associations between levels of antibodies against A. actinomycetemcomitans and P. gingivalis and the presence of coronary heart disease within large population-based cohorts [2123].…”
Section: Introductionmentioning
confidence: 99%
“…23 For the purpose of epidemiological studies, 3 clinical parameters are typically recorded to assess the prevalence of PD: (1) Bleeding on probing, (2) pocket depth, and (3) clinical attachment level, which reflects the amount of periodontal tissue loss. 3 Other markers of periodontitis include detection of subgingival microbial colonization by selected periodontal organisms [24][25][26][27] and evaluation of serum IgG or IgA antibodies to selected periodontal bacteria [28][29][30][31][32][33][34][35] . to 10-fold higher rates of myocardial infarction and death before the age of 40 years.…”
Section: (Figure 1)mentioning
confidence: 99%